Radiographic assessment of the health status of first permanent molars in pediatric groups in a Nigerian tertiary health institution: a retrospective cross-sectional study. (Nigerian Dental Journal, 2025)
Background: The first permanent molars (FPMs) are critical for maintaining normal masticatory functions and dentofacial harmony. However, they are highly susceptible to dental caries, especially in pediatric populations. This study aimed to radiographically assess the health status of first permanent molars in children aged 7 to 16 years at a Nigerian tertiary health institution, focusing on caries prevalence, structural anomalies, and periapical health.Study Design: A retrospective cross-sectional of study panoramic radiographs was conducted.Setting: Department of Oral Diagnostic sciences, Aminu Kano Teaching Hospital, Nigeria from January 2022 to December 2023, following ethical approval from the hospital's research and ethics Committee (approval number NHREC/29/01/2025/AKTH/EC/4004).Participants: 317 children aged 7-16 years with mean age of approximately 11 years (SD = 3.26), 142 males (45.2%) and 172 females (54.8%) with artefact-free radiographs.Outcome Measures: Primary: Caries prevalence. Secondary: Restoration status, missing, periapical pathology (rarefying osteitis), and structural anomalies (hypomineralization/fusion/taurodontism). Key Results:Caries: Overall caries prevalence across all first permanent molars was 36.9% (117/314); highest in mandibular molars 17.2% in mandibular left first permanent molar  and 11.8% mandibular right first permanent molar , suggesting a greater predisposition of mandibular molars to carious lesions.Restorative Interventions: were noted in only 5.4% (17/314) of the first permanent molars , with mandibular right first permanent molar  exhibiting the highest frequency of restorations.Missing Teeth: was infrequent, with the highest incidence 2.5% (8/314) observed in mandibular right first permanent molar.Periapical Health: 95.2% (302/314) of cases were free of pathology, while 4.5% (14/314) predominantly ages 15-16, presented with rarefying osteitis, predominantly among individuals aged 15–16 years.Structural Anomalies: Low frequencies, including hypomineralization 1%, (3/314), fusion 0.6%, (2/314), and taurodontism 1%, (3/314).Conclusion: The findings suggest that while most first permanent molars remain structurally sound, caries prevalence is higher in mandibular molars, with limited restorative intervention observed. The low rates of periapical pathologies and structural anomalies indicate relatively good oral health, though older children showed increased susceptibility to dental decay and rarefying osteitis. These results highlight the need for preventive strategies, early intervention, and improved access to dental care to enhance pediatric oral health outcomes.